(untitled) (Ameghiniana, 2014)
Cut and fill (gutter-casts) and similar circular or furrow-like structures from the Early Ordovician (Acoite Formation) of the Cordillera Oriental of Northwestern Argentina are described and interpreted throughout a combined sedimentologic, paleoecologic, and taphonomic analysis. The Acoite Formation is about 2000 m thick and represents a storm-dominated shelf depositional system. Gutter-cast s. filled with sandstones and coquinas are dominant in muddy facies in the middle and upper parts of the unit. The analysis of the morphology and internal structures of the gutter-casts suggests a composite origin for both the erosive and depositional phases involved in the formation of these structures. The erosive events are interpreted as produced by strong storm-surge ebb currents, which drag the bottom with secondary helical flows superimposed to characteristic combined flows present on the shelf. A detailed bioestratinomic study allows the distinction of various kinds of coquinas filling the furrows. Some are mainly allochthonous and othermainly autochthonous or parautochthonous. Taking into account their segregation, sorting, reorientation, mechanical abrasion and fragmentation, a variable degree of mixing has been determined. Life habits and preferences of the organisms colonizing the furrows account for a strong habitat alteration. The paleoecologic features of autochthonous and parautochthonous concentrations indicate a significant faunal turnover in relation to the sorrounding autochthonous assemblages of the muddy shelf.